Features of a Strategic Approach to Human Resource Management (International Journal of Management and Sustainability, 2015)
Success of strategic human resource management is considered from the point of view of existence of negative qualities of firm personnel. Such parameters of employees, as commitment to stereotypes of group behavior, stay in the field of ordinary consciousness, the low level of personal culture and lack of skills of logical thinking are considered. Convolution matrix with parameters staff proposed for use as a measure of the success of management. It is established that firms numbering personnel from 45 to 85 people can be the most successful for Russia on this indicator.